Gambaran Korupsi Mahasiswa Prodi MIK di STIKes Santa Elisabeth Medan - Theresia Elen Novia Ziraluo; Febina Sintiya Br Sembiring (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Time corruption is a phenomenon that refers to actions or activities that waste or squander time without providing value or useful results. Time corruption is something that is difficult to find, especially in students who are still not good at carrying out their duties well. This research aims to see the picture of corruption during the MIK study program students at STIKes Santa Elisabeth Medan. This research uses a descriptive design with a quantitative approach. The sample in this study amounted to 30 people. In this research, researchers collected data using a questionnaire. This research was conducted in March 2023. Data was analyzed univariably. The research results showed that there were 12 students who had good and good times of corruption (40%), 11 people had sufficient times of corruption (36.67) and 7 people experienced corruption when they were poor (23.33). In this case, MIK students must continue to maintain and implement the time corruption that has been carried out and try to properly improve the time corruption that is still being carried out.